New occurrences of lithodid crabs (Crustacea: Decapoda: Lithodidae) from the coasts of Africa, with the description of a new species of Paralomis White, 1856 - Muñoz, Isabel; García-Isarch, Eva (Zootaxa, 2013)
The Collection of Decapod and Stomatopod Crustaceans from the Cádiz Oceanographic Centre (CCDE-IEOCD) compris-es a number of lithodid crabs from Spanish surveys carried out in African waters. The revision of this material allowed the confirmation of new records of Lithodes ferox Filhol, 1885 in Guinea–Bissau and Mauritania, Lithodes mamillifer Macpherson, 1988 in Mozambique, Neolithodes asperrimus Barnard, 1947, Neolithodes grimaldii (A. Milne Edwards & Bouvier, 1894) and Paralomis erinacea Macpherson, 1988 in Mauritania, Paralomis africana Macpherson, 1982 in Na-mibia and Paralomis cristulata Macpherson, 1988 in Guinea–Bissau. Some of these records contribute to extent the geo-graphical and/or bathymetrical range of the species. One new species of the genus Paralomis from Namibia is described and illustrated. This species shows close affinity with its congener Paralomis pectinata Macpherson, 1988, from Venezu-ela. The morphological differences between the two species are included.